Lessons from typhoon Ondoy technical and socio-cultural rationality in risk communication - Tanseco, Oliver Sy 1972- (2012)
"The study sought to determine the importance of technical and socio-cultural dimensions in the plans formulated and implemented by the national agency and the local government units during and after the onset of typhoon Ondoy and how such plans and procedures were perceived and whether or not they were followed by the residents of the subject barangays. The study used the mixed-method research design, using both quantitative and qualitative research methods. The communication strategies used during the occurrence of typhoon Ondoy in September 2009 in Barangay Catmon in Malabon City, Metro Maila and Barangay Malinta in Los Banos, Laguna were determine. Malabon and Los Banos, Laguna are both identified as flood-prone areas. For the quantitative part of the study, the researchers used a structured questionnaire to gather media exposure, media preferences, risk perception, risk behaviour and coping mechanisms of the residents living in the most vulnerable sites of the barangays. For the qualitative part of the study, focused group discussions (FGD) with residents who had been affected by typhoon Ondoy in each area/barangay were conducted to determine the communication strategies employed by government and other sectors and how they described their values, perspectives, experiences, local knowledge and cultural beliefs on risk and risk communication. Focus interview was conducted with key NDRRMC, city planning office and barangay officials. The study results and findings showed that the information campaign of the NDRRMC in terms of communicating preparation and mitigation procedures for flood risks was still lacking and there was a need to intensify it. This was far from the current perception of the study participants and respondents that NDRRMC only provides training program. Media plays a vital role in the lives of the people, particularly during disasters. People rely on media reports and therefore, media should be responsible in disseminating accurate and timely information. While NDRRMC communicated with media through telephone, mobile phones, fax and press conferences and interviews, the practice should be reviewed and institutionalized. Coordination between the local government units and the barangays had also been important during disasters, as well as the barangays' communication system with their constituents. The Ondoy experience showed that there was absence of an effective communication system in the barangays. Perceived reasons for this were the lack of funds to acquire the needed equipment, the lack of regular disaster coordination staff and the inability of the barangay officials to implement an effective disaster management plan. The perceived inaccuracy of information given out especially by PAGASA, implied that the people do not fully understand the meaning of the warning signals. In addition, the preparedness of the residents in flood-prone areas was only based on their experience from past typhoons and not on the worst possible scenarios. Because of the scope and extent of floods brought by typhoon Ondoy, designated evacuation centers were not enough. The local government units, aided by the national government should provide a permanent site or sites for evacuation centers. The Seal of Disaster Preparedness (SDP) initiated by the Department of Interior and Local Government (DILG) is goven to LGUs after a series of assessment to determine their performance and compliance in institutionalizing disaster preparedness. This program of recognizing deserving individual, organizations to include the LGUs should be replicated by other department, agencies and bureaus of the national and local government. Other department must also be assessed and evaluated on the level of disaster preparedness of their respective bureaus and agencies within their scope of control. This will include not only agencies that directly complement the NDRRMC efforts during actual disaster but other sectors of civil service. An ideal communication plan for all types of disaster is the key to a zero-casualty Philippines during human-generated and natural calamities. The study clearly identified the need for policymakers of national and local government agencies responsible for disaster risk and reduction management to take into consideration not only the technical but also the socio-cultural rationality of the particular locality where a specific communication material will be implemented."